Correlation between traditional enhancement protocols, used in the identification anaerobic threshold for cyclists: a critical analysis - Urso, José Eduardo (2012)
Introduction: The cycling is a sport that has its own characteristics, among them we can say that the integration of several factors define the athlete, where the biomechanics of movement, ergonomics, physiology and technology of materials, influence the efficiency of the athlete. These cases not considered in laboratory tests may significantly affect the dataobtained. Review of Literature: I reviewed the articles that made use of these protocols and found a relationship between the various protocols and methodologies, thereby identifying the contents of variables and their correlations. With the development of the research can see that in most tests used in the articles studied, cite some characteristics that make the protocols have a certain similarity with respect to the methodology employed. Factors such as type of cycle, initial power, increase of load, cadence, time between stages and total time of testing, lead us to understand how these protocols are distant from the reality of proof. Conclusion: Through the study we can conclude that the relationship between laboratory tests using traditional protocols and specific incremental cycling competition this far away from the specificity of sport in question. With regard to maximum effort tests presented and discussed in the literature, there are very important items and should be taken into account by researchers such as initial charge, an increase of load, time of placement, and rhythm that make us think that these variables can interfere with the final result of the test.